Corrosion Inhibition of Mild Steel In (1 M Hcl) Solution Using Plant Extract and The Synergistic Effect of Iodide Ions - Safaa I. Daaj; Ahmed N. Abd (Academic Science Journal)
The corrosion inhibitive impacts of a mixture (4:1) of Citrus Limon leaf (CLL) extract and potassium iodide additives when the mild steel was exposed to the corrosive solution (1M HCl) were evaluated using the weight-loss method at temperatures of )303, 313, 323, and 333( K. It was noted that the mixture acts as an inhibitor of mild steel corrosion at concentrations of )1.25, 2.5, 3.75, 5, and 6.25( ml/L. It was observed also that the inhibition efficiency (%I) of the mixture increased with an increase in temperature in the presence of the synergistic effect of the iodide ion. It was found that at the highest mixture concentrations and temperatures, the inhibition competence increased to 95.20%. Inhibitor adsorption characteristics were reached by the Langmuir isotherm and were compatible. The adsorption thermodynamic parameters that were calculated supported the mixed-adsorption of the mixture on a mild steel surface. A surface analysis technique (SEM) used to confirm the occurrence of an adsorption process on the surface.